Acquisition of the Korean Imperfective Aspect Markers –ko iss– and –a iss– by Japanese Learners: A Multiple‐Factor Account. Issue 4 (27th August 2015) - Ryu, Ju‐Yeon; Horie, Kaoru; Shirai, Yasuhiro
Abstract : Although cross‐linguistic research on second language tense‐aspect acquisition has uncovered universal tendencies concerning the association between verbal semantics and tense‐aspect markers, it is still unclear what mechanisms underlie this link. This study investigates the acquisition of two imperfective aspect markers (– ko iss – and – a iss –) in Korean by Japanese learners to determine how cognitive universals, first language (L1) transfer, and input frequency interact. The current findings are compared with the results of Lee and Kim (2007), who studied the acquisition of the same aspect markers by L1 English learners. Both groups of learners acquired the progressive – ko iss – earlier than the resultative – a iss –/– ko iss –, while L1 Japanese learners acquired the resultative use of – ko iss – earlier than L1 English learners. Japanese learners' early acquisition of the resultative – ko iss – is likely due to L1 transfer, because Japanese has a similar imperfective marker (– te i –). We argue that cognitive universals (one‐to‐one principle), L1 transfer, and input frequency all contribute to the acquisition patterns of temporal morphology.